Indo-European nominal o-stems and question of their origin - Blažek, Václav (Lingua Posnaniensis, 2015)
In the article the most productive formation of the Indo-European nominal declension, the o-stems, are described and analyzed. Two competing interpretations are discussed. One of them is finally preferred with respect to external typological parallels.